Laws of the sea the creation and implementation of municipal fishery ordinances in Miagao, Iloilo (1998-2015). - Cordero, Cyril D (2016.)
This study examines the assertion of local government against the national government in terms of the creation and implementation of municipal fishery ordinances. The local government of Miag-ao showed soft resistance against the national government did not follow the all provisions provided by the national government through the Philippine Fisheries Code of 1998. Second, the local government created the Revenue Code, is a set of fines and penalties, and did not adopt the provisions given by the national government. Using the dynamics of Migdal?s theory, the local government asserts itself against the national government. This is evident in the municipality of Miag-ao.
Research Paper (Undergraduate, Bachelor of Arts in History) College of Arts and Sciences,University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Municipal Fishery Ordinances -- Miagao, Iloilo